People and Nation: Spain in Eighteenth-Century Cordel Literature - Gomis Coloma, Juan (Cuadernos de Historia Moderna, 2012)
This article explores the contribution that eighteenth century cordel literature played in the construction of a national identity in Spain, analyzing several broadsides with patriotic content while discussing the role played by politics in this process. Finally, it approaches the cultural process by which, in the nineteenth century, popular literature was transformed by the intellectual elite into one of the main pillars in the process of Spanish national identity construction.
Keywords: Cordel Literature; Popular Literature; Ballads; National Building; Nation.